Research on Key Technology of INSAS Console System - Kun Fang; Jinsong Tang; Sen Zhang (Institute of Advanced Engineering and Science, 2014)
INSAS Console System was designed to receive a large amount of data of interferometric synthetic aperture sonar. This paper mentions multithreading technology and data pool technology, which could solve a series of problem such as data transmission and memory consumption to guarantee 2D image and 3D graphic of INSAS display fluently in the system. The example of the INSAS Console System is shown in the end of the paper. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4008